The effect of low-abundance OTU filtering methods on the reliability and variability of microbial composition assessed by 16S rRNA amplicon sequencing - Nikodemova, Maria; Holzhausen, Elizabeth A.; Deblois, Courtney L.; Barnet, Jodi H.; Peppard, Paul E.; Suen, Garret; Malecki, Kristen M. (Frontiers in Cellular and Infection Microbiology, 2023)
PCR amplicon sequencing may lead to detection of spurious operational taxonomic units (OTUs), inflating estimates of gut microbial diversity . There is no consensus in the analytical approach as to what filtering methods should be applied to remove low abundance OTUs; moreover, few studies have investigated the reliability of OTU detection within replicates. Here, we investigated the reliability of OTU detection (% agreement in detecting OTU in triplicates) and accuracy of their quantification (assessed by coefficient of variation (CV)) in human stool specimens. Stool samples were collected from 12 participants 22-55 years old. We applied several methods for filtering low abundance OTUs and determined their impact on alpha-diversity metrics. The reliability of OTU detection without any filtering was only 44.1 % (SE=0.9) but increased after filtering low abundance OTUs. After filtering OTUs with < 0.1% abundance in the dataset, the reliability increased to 87.7% (SE=0.6) but at the expense of removing 6.97% reads from dataset. When filtering was based on individual sample, the reliability increased to 73.1% after filtering OTUs with < 10 copies while removing only 1.12% of reads. High abundance OTUs (> 10 copies in sample) had lower CV, indicating better accuracy of quantification than low abundance OTUs. Excluding very low abundance OTUs had a significant impact on alpha-diversity metrics sensitive to the presence of rare species (Observed OTUs, Chao1) but had little impact on relative abundance of major phyla and families and alpha-diversity metrics accounting for both richness and evenness (Shannon, Inverse Simpson). To increase the reliability of microbial composition we advise removing OTUs with < 10 copies in individual samples, particularly in studies where only one subsample per specimen is available for analysis.